Novel copolymers of styrene. 9. Fluoro ring-disubstituted butyl 2-cyano-3-phenyl-2-propenoates. Issue 4 (2nd April 2016) - Kharas, Gregory B.; Schjerven, William S.; Baray, Uriel A.; Chan, Samantha; Cole, Michael T.; Haddad, Alexander F.; Lucente, Joseph A.; Patterson, Kayne J.; Ralko, Arthur; Reget, Katie N.; Shamblen, Catherine A.; Whitmore, Emily M.
ABSTRACT: Electrophilic trisubstituted ethylenes, ring-disubstituted butyl 2-cyano-3-phenyl-2-propenoates, RPhCH˭C(CN)CO2 C4 H9 (where R is 2-fluoro-5-methoxy, 2-fluoro-6-methoxy, 3-fluoro-4-methoxy, 4-fluoro-3-methoxy, 5-fluoro-2-methoxy, 3-fluoro-2-methyl, 3-fluoro-4-methyl, 4-fluoro-2-methyl, 4-fluoro-3-methyl, 5-fluoro-2-methyl were prepared and copolymerized with styrene. The monomers were synthesized by the piperidine catalyzed Knoevenagel condensation of ring-disubstituted benzaldehydes and butyl cyanoacetate, and characterized by CHN analysis, IR, 1 H and 13 C-NMR. All the ethylenes were copoly-merized with styrene (M1 ) in solution with radical initiation (ABCN) at 70°C. The compositions of the copolymers were calculated from nitrogen analysis and the structures were analyzed by IR, 1 H and 13 C-NMR. Decomposition of the copolymers in nitrogen occurred in two steps, first in the 200–500°C range with residue (1.2–3.5% wt.), which then decomposed in the 500–800°C range.